Microbial fuel cells as an alternative energy source: current status. Issue 2 (3rd July 2018) - Javed, Muhammad Mohsin; Nisar, Muhammad Azhar; Ahmad, Muhammad Usman; Yasmeen, Nighat; Zahoor, Sana
ABSTRACT: Microbial fuel cell (MFC) technology is an emerging area for alternative renewable energy generation and it offers additional opportunities for environmental bioremediation. Recent scientific studies have focused on MFC reactor design as well as reactor operations to increase energy output. The advancement in alternative MFC models and their performance in recent years reflect the interests of scientific community to exploit this technology for wider practical applications and environmental benefit. This is reflected in the diversity of the substrates available for use in MFCs at an economically viable level. This review provides an overview of the commonly used MFC designs and materials along with the basic operating parameters that have been developed in recent years. Still, many limitations and challenges exist for MFC development that needs to be further addressed to make them economically feasible for general use. These include continued improvements in fuel cell design and efficiency as well scale-up with economically practical applications tailored to local needs.